Pilietinės aplinkosaugos iniciatyvos ir judėjimai pasitelkus naująsias medijas - Petrauskaitė, Indrė (Information & Media, 2012)
Pilietinis dalyvavimas ir aktyvus piliečių įsitraukimas į valstybės politinį gyvenimą įvairiomis pilietinio dalyvavimo formomis yra neatskiriama tvaraus valdymo ir darnaus vystymosi dalis. Valstybėse vykdomi regionų plėtros projektai vis dažniau grindžiami darnaus vystymosi principais, ir vienas iš pagrindinių veiksnių – piliečių dalyvavimo skatinimas ir dalyvavimo formų priemonių užtikrinimas. Todėl vis daugiau dėmesio skiriama internetui ir naujosioms medijoms, kurios leidžia piliečiams lengviau bendradarbiauti, savo nuomonę svarbiais visuomeniniais klausimais pasakyti iniciatyvų internetinėje erdvėje būdu. Išpopuliarėjus socialinių tinklų svetainėms, medijoms tapus lengviau prieinamoms kiekvienam piliečiui, pasaulyje ėmė daugėti pilietinių iniciatyvų, kurios kartais peraugdavo į pilietinius judėjimus ar net revoliucijas. Straipsnyje remiantis socialinių tinklų, viešosios erdvės teorijomis siekiama nustatyti, kokią įtaką internetas ir naujosios medijos daro aplinkosaugos problemų sprendimui pilietiniu lygmeniu. Reikšminiai žodžiai: aplinkosauga, pilietinės iniciatyvos, naujosios medijos, socialiniai tinklai, viešoji erdvė, internetas, socialinių tinklų svetainės. Environmental Initiatives and Movements in the Context of new Media’s Possibilities Indrė Petrauskaitė Summary Civic engagement and active involvement in the political life of the various forms of participation is an integral part of sustainable government and sustainable development. Nowadays, the state should encourage ensuring the principles of sustainable development. One means to do it is promoting Citizen’s participation and its forms. A growing attention given to the Internet and new media through which the citizens can cooperate, their views on important issues and initiatives can take the online space for discussions and movements. Social networking websites, new media getting more and more popular every day hold a prominent place in the lives of a large number of people. That is why citizen in the world began to increase overall civic initiatives, which sometimes degenerate into civil movements or even revolutions. This paper examines the concept of civic participation and the impact of new media and the Internet on environmental initiatives and movements. The article is dedicated showing how the new media and the Internet influence civil participation in environmental issues. It discusses few important components of civil participations: the level of civil society, social capital, social networks, public space, and defines changes of each level which are determined by the new media and the Internet. Also, the article explores changes of issues of environmental initiatives and movements and defines the fundamental changes that influence the growth of environmental movements nowadays. The research and conclusions on the impact of the new media and the Internet on environmental initiatives are strengthen by academic observations and examples of environmental movements. Keywords: environmental initiatives and movements, civil initiatives, new media, social networks, public space, the Internet, sites of social networks.